Beacons of hope : youths and their contribution to the development of the theatre industry in Zimbabwe - Rwafa, Urther (2016)
Since independence (attained in 1980), the theatre industry in Zimbabwe has experienced some tremendous changes due to the involvement of youths who have the capacity to experiment with different genres, such as theatre in the park, street theatre, forum theatre, proscenium theatre and community theatre. All these forms of theatre continue to explore different themes and perspectives that affect Zimbabwean youths in both positive and negative ways. This article explores factors that affect the productive life of theatrical productions in Zimbabwe paying particular attention to the extent to which youths were/are involved in contributing to the growth of the theatre industry in Zimbabwe. In this endeavour, the article will focus on education and training aspects, networking, collaborations, funding, research, theatre impact and advocacy. A better understanding of how the above-mentioned factors affect the developmental skills of youths and the growth of Zimbabwean theatre industry will create awareness among youths, who should make informed decisions if they are to survive 'cut-throat' competition in Zimbabwe's theatre industry.